2021
DOI: 10.5114/wiitm.2021.103955
|View full text |Cite
|
Sign up to set email alerts
|

Robotic single-site surgery versus laparoendoscopic single-site surgery in early-stage endometrial cancer: a case-control study.

Abstract: Introduction: Laparoendoscopic single-site surgery (LESS) can reduce the limited invasiveness of conventional laparoscopy while providing superior cosmetic results. Robotic single-site surgery (RSSS) can overcome this shortcoming to a certain extent. Aim: To evaluate the advantages of RSSS in treating early-stage endometrial cancer by comparing RSSS with LESS. Material and methods: From January 2018 to August 2018, patients diagnosed with endometrial cancer from endometrial curettage and imaging studies were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…This procedure can also be performed in any hospital. 35 Research has shown that LESS surgery results in higher prefrontal beta power during suturing, compared with other methods. 36 To assess the ergonomic stress on surgeons, various methods have been employed in the literature, including surface electromyography (sEMG) to measure muscle activity; 37 hand function models for analyzing tendon and joint forces, electromyographic (EMG) activity; 38 and assessments of posture, activity, tools, and handling, as well as eye tracking to evaluate cognitive variations in surgical scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure can also be performed in any hospital. 35 Research has shown that LESS surgery results in higher prefrontal beta power during suturing, compared with other methods. 36 To assess the ergonomic stress on surgeons, various methods have been employed in the literature, including surface electromyography (sEMG) to measure muscle activity; 37 hand function models for analyzing tendon and joint forces, electromyographic (EMG) activity; 38 and assessments of posture, activity, tools, and handling, as well as eye tracking to evaluate cognitive variations in surgical scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, laparoscopic hysterectomy offers several advantages over robotic‐assisted hysterectomy, including lower cost, shorter surgical time, fewer ports needed, and similar outcomes. This procedure can also be performed in any hospital 35 …”
Section: Discussionmentioning
confidence: 99%
“…With the introduction of the da Vinci robotic system, the combination of a robot system and a single port platform will overcome many of the challenges in single-port surgery, such as instrument crowding and the need for highly advanced laparoscopic skills ( 32 , 33 ). However, robotic surgery remains relatively expensive, single-port laparoscopic surgery may be a more relevant option for our patients, but it does pose a challenge to the surgeon’s surgical skills.…”
Section: Discussionmentioning
confidence: 99%
“…Sun H et al [59] demonstrated in 2021 that robotic singlesite surgery (RSSS) for early-stage endometrial cancer was feasible and safe. It also reduced significantly operating time, blood loss, and hospital stay compared to LESS[59]. The RSSS group had considerably longer pre-surgical time (8 min vs. 2 min, p < 0.05), lower blood loss (Me = 50 mL vs. 85 mL, p < 0.05), and much shorter vaginal cuff closure time (21 min vs. 30 min, p < 0.05) than the LESS group.…”
mentioning
confidence: 89%